'It's just one big vicious circle': young people's experiences of highly visual social media and their mental health. Issue 3 (11th May 2022) - McCrory, Alanna; Best, Paul; Maddock, Alan
Abstract: Highly visual social media (HVSM) platforms, such as Snapchat, Instagram and TikTok, are increasingly popular among young people. It is unclear what motivates young people to engage with these specific highly visual platforms and what impact the inherent features of HVSM have on young people's mental health. Nine semi-structured focus group sessions were conducted with males and females aged 14 and 15 years ( n = 47) across five secondary schools in Northern Ireland. Thematic analyses were conducted, and a conceptual model was developed to illustrate the findings. This study found that features such as likes/comments on visuals and scrolling through a feed were associated with the role of 'viewer', instigating longer-lasting feelings of jealousy, inferiority and pressure to be accepted. To combat these negative emotions, young people turn to the role of 'contributor' by using filters, selecting highlights to post to their feed and adjusting their personas, resulting in temporary feelings of higher self-esteem, greater acceptance and popularity. As users of HVSM are constantly switching between the role of viewer and contributor, the emotions they experience are also constantly switching between instant inadequacy and instant gratification. HVSM appears to trigger an unrelenting process of emotional highs and lows for its adolescent users.